Intranasally Administered Human MSC-Derived Extracellular Vesicles Pervasively Incorporate into Neurons and Microglia in both Intact and Status Epilepticus Injured Forebrain - Kodali, Maheedhar (Int J Mol Sci, 2019)
Extracellular vesicles (EVs) derived from human bone marrow mesenchymal stem cells (hMSCs) have great promise as biologics to treat neurological and neurodegenerative conditions due to their robust antiinflammatory and neuroprotective properties. Besides, intranasal (IN) administration of EVs has caught much attention because the procedure is noninvasive, amenable for repetitive dispensation, and leads to a quick penetration of EVs into multiple regions of the forebrain. Nonetheless, it is unknown whether brain injury-induced signals are essential for the entry of IN-administered EVs into different brain regions. Therefore, in this study, we investigated the distribution of IN-administered hMSC-derived EVs into neurons and microglia in the intact and status epilepticus (SE) injured rat forebrain. Ten billion EVs labeled with PKH26 were dispensed unilaterally into the left nostril of naïve rats, and rats that experienced two hours of kainate-induced SE. Six hours later, PKH26 + EVs were quantified from multiple forebrain regions using serial brain sections processed for different neural cell markers and confocal microscopy. Remarkably, EVs were seen bilaterally in virtually all regions of intact and SE-injured forebrain. The percentage of neurons incorporating EVs were comparable for most forebrain regions. However, in animals that underwent SE, a higher percentage of neurons incorporated EVs in the hippocampal CA1 subfield and the entorhinal cortex, the regions that typically display neurodegeneration after SE. In contrast, the incorporation of EVs by microglia was highly comparable in every region of the forebrain measured. Thus, unilateral IN administration of EVs is efficient for delivering EVs bilaterally into neurons and microglia in multiple regions in the intact or injured forebrain. Furthermore, incorporation of EVs by neurons is higher in areas of brain injury, implying that injury-related signals likely play a role in targeting of EVs into neurons, which may be beneficial for EV therapy in various neurodegenerative conditions including traumatic brain injury, stroke, multiple sclerosis, and Alzheimer’s disease.